2010
DOI: 10.1002/msj.20215
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Immunotherapy

Abstract: Melanoma immunotherapy has been an area of intense research for decades, and this work is now yielding more tangible results for patients. Work has focused on 4 main areas: cytokine therapy, administration of immune-modulating antibodies, adoptive T-cell therapy, and vaccines. Cytokine therapy is an established treatment for advanced melanoma, and immune-modulating antibodies have recently emerged as an exciting new area of drug development with efficacy now established in a phase III trial. Adoptive T-cell th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 108 publications
0
25
0
Order By: Relevance
“…This section will briefly highlight some of the successes and issues with current immunotherapy, and try to determine how these deficiencies may be overcome. A more complete review of melanoma immunotherapy strategies can also be found from Sivendran et al (Sivendran et al, 2010 (Fang et al, 2008). IL-2 therapy remains the only immunotherapy strategy for late stage melanoma but significant issues remain with its use.…”
Section: Issues With Immunotherapymentioning
confidence: 99%
See 4 more Smart Citations
“…This section will briefly highlight some of the successes and issues with current immunotherapy, and try to determine how these deficiencies may be overcome. A more complete review of melanoma immunotherapy strategies can also be found from Sivendran et al (Sivendran et al, 2010 (Fang et al, 2008). IL-2 therapy remains the only immunotherapy strategy for late stage melanoma but significant issues remain with its use.…”
Section: Issues With Immunotherapymentioning
confidence: 99%
“…Cytokines like IL-15, IL-7, and IL-21 could prove more beneficial in stimulating antitumor immune cells during chemotherapy, with reduced toxicity when compared to IL-2 or IFN (Epardaud et al, 2008;Ribas, 2006). IL-21 has the added benefit of more selective T cell expansion versus IL-2, in which Tregs are not responsive to IL-21 stimulation (Sivendran et al, 2010). Currently IL-21 is being tested in phase I/II clinical trials displaying promising results (Sivendran et al, 2010).…”
Section: Treatment Of Metastatic Melanoma 132mentioning
confidence: 99%
See 3 more Smart Citations